>10% solar-to-hydrogen efficiency unassisted water splitting on ALD-protected silicon heterojunction solar cells. Issue 6 (25th April 2019) - Tan, Chor Seng; Kemp, Kyle W.; Braun, Michael R.; Meng, Andrew C.; Tan, Wanliang; Chidsey, Chris E. D.; Ma, Wen; Moghadam, Farhad; McIntyre, Paul C.
Abstract : We demonstrate unassisted water splitting with >10% solar-to-hydrogen conversion efficiency using series-connected silicon heterojunction solar cells protected by ALD TiO2 in a novel, integrated device architecture. Abstract : Solar water splitting using photoelectrochemical cells (PEC's) is a promising pathway toward clean and sustainable storage of renewable energy. Practical realization of solar-driven synthesis of hydrogen and oxygen integrating light absorption and electrolysis of water has been challenging because of (1) the limited stability of good photovoltaic materials under the required electrochemical conditions, and (2) photovoltaic efficiency losses due to light absorption by catalysts, the electrolyte, and generated bubbles, or reflection at their various interfaces. Herein, we evaluate a novel integrated solar water splitting architecture using efficient silicon heterojunction photovoltaic cells that avoids such losses and exhibits a solar-to-hydrogen (STH) efficiency in excess of 10%. Series-connected silicon Heterojunction with Intrinsic Thin layer (HIT) cells generate sufficient photovoltage for unassisted water splitting, with one of the cells acting as the photocathode. Platinum is deposited on the back (dark) junction of this HIT cell as the catalyst for the hydrogen evolution reaction (HER). The photocathode is protected from corrosion by a TiO2 layer deposited by atomic layer deposition (ALD) interposed between the HIT cell and the Pt, enabling stable operation for >120 hours. Combined with oxygen evolution reaction (OER) catalysts deposited on a porous metal dark anode, these PEC's achieve stable water splitting with a record high STH efficiency for an integrated silicon photosynthesis device.